Design and Stress Analysis of a System for Cleaning Needle Electrodes for Radiofrequency Ablation during Surgeries - Chrobok, Jan; Schmidt, Martin; Penhaker, Marek; Kubicek, Jan; Hlavackova, Milada; Vavra, Petr; Ihnat, Petr (2019 IEEE 17th World Symposium on Applied Machine Intelligence and Informatics (SAMI), 2019)
The aim of this work was to design a system of needle cleaning for radiofrequency ablation tools in order to replace the current cleaning methods, which use ordinary sandpaper. This method of cleaning is time-consuming, and therefore needs to be replaced. The greatest benefit of the solution would be the speed and ease of cleaning during surgeries.